Exploring critical television literacy skills in a tenth graders’ classroom - Esteban Núñez, María Teresa (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This study was aimed at providing tenth graders with spaces and activities to develop critical television literacy skills. This was the first time that students at Antonio Nariño School in Moniquirá, were involved in the analysis of TV programs. Therefore, this activity allowed them to establish a new type of interaction between the TV programs and their personal and familiar worlds. A descriptive case study was conducted and the data analysis reported that teenagers are in a process of building up their personalities and identities. In this process, they ask their closer realities and identify in the sitcoms representations of the reality and spaces to learn about academic issues as well as guides to solve daily life problems.